Salvage total glossectomy and total glosso-laryngectomy: Are they worth it? A GETTEC French multicenter study. - Mazerolle, Paul; Fuchsmann, Carine; Schultz, Philippe; Benmoussa, Nadia; Malard, Olivier; Bozec, Alexandre; Deneuve, Sophie; Folia, Mireille; Perreard, Marion; Lasne-Cardon, Audrey; Chabrillac, Emilien; Vergez, Sebastien; et al. (Oral Oncology, 2022)
BACKGROUND: Salvage total glossectomy (TG) or total glosso-laryngectomy (TGL) remain controversial, as highly morbid procedures. The objective was to describe oncological and functional outcomes after salvage TG or TGL. METHODS: We performed a multicenter retrospective study, including patients with previous neck irradiation undergoing TG or TGL for squamous cell carcinoma involving the base of tongue. RESULTS: We included 42 patients: 27 in the TG group and 15 in the TGL group. For the entire cohort, median OS and DFS were estimated at 19 months (95% IC [14-44]) and 10 months (95% IC [7-13]) respectively, with no difference between the two groups. After a median follow-up of 90 months, 10 patients (24%) were alive and free of disease. Att he end of follow-up, we noted a gastrostomy dependency of 89% and 87 %respectively in the TG and TGL group, and 48% of patients in the TG group had a tracheotomy. CONCLUSION: Although local control is difficult to achieve after salvage TG or TGL, these procedures are associated with acceptable survival and chance of cure for a last-resort situation. TG and TGL can be proposed in selected motivated patients after careful shared decision-making.
EVALuna2:520877